2014
DOI: 10.1007/s00520-014-2462-2
|View full text |Cite
|
Sign up to set email alerts
|

Dietary habits changes and quality of life in patients undergoing chemotherapy for epithelial ovarian cancer

Abstract: Women undergoing chemotherapy for ovarian cancer change their dietary habits in a pro healthy direction, and these changes are more expressed in patients undergoing subsequent-line chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 28 publications
2
11
1
1
Order By: Relevance
“…[ 20 ] gastrointestinal symptoms (nausea indicated in 39%, vomiting in 27% and constipation in 41% of patients) potentially influencing weight loss are prevalent early in the course of cancer patients with regard to lower caloric intake, nutritional status and prior therapy experience. However, in current study only small percentage of patients was underweight, which stay in line with previously published data [ 11 , 21 ]. In early 90’s has been already indicated that a significant percentage of patients who even received exclusive oral feeding did not cover a minimum acceptable quantity of their energy requirements [ 22 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…[ 20 ] gastrointestinal symptoms (nausea indicated in 39%, vomiting in 27% and constipation in 41% of patients) potentially influencing weight loss are prevalent early in the course of cancer patients with regard to lower caloric intake, nutritional status and prior therapy experience. However, in current study only small percentage of patients was underweight, which stay in line with previously published data [ 11 , 21 ]. In early 90’s has been already indicated that a significant percentage of patients who even received exclusive oral feeding did not cover a minimum acceptable quantity of their energy requirements [ 22 ].…”
Section: Discussionsupporting
confidence: 93%
“…However, none from the examined patients consumed such products, which could not influence the obtained results of energy intake. We have already reported in previously published study that patients suffering from ovarian cancer did not reach even 25 kcal per kg of body weight during the day [ 11 ]. The changes in energy and nutrients intake are especially visible when we take into account separated cycles of cytotoxic chemotherapy [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the 2006 European Society for Parenteral and Enteral Nutrition (ESPEN) non-surgical oncology guidelines on enteral nutrition suggest that cancer patients should consume at least 1.2-2.0 g protein/kg body weight per day (16), most cancer patients do not reach this level via the diet and/or through nutritional supplementation (11, 17, 18). Besides a reduced appetite (19, 20), the available nutritional supplements for cancer patients are often energy-dense and have a limited amount of high quality protein.…”
Section: Introductionmentioning
confidence: 99%
“…While less than 10% of women are underweight, 56 30% to 67% are malnourished at diagnosis, based on nutrition assessment tools such as the Patient-Generated Subjective Global Assessment and the Nutritional Risk Index. 44,52,57,58 The presence of ascites and a high body fat percentage at any time point will ''inflate'' BMI values and mask muscle wasting, a consequence of malnourishment. 59 In addition to BMI, body composition measures can provide much needed objective data to identify OC survivors with low muscle mass and/or excess body fat in need of dietary and exercise interventions.…”
Section: Body Weightmentioning
confidence: 99%